Upaya Peningkatan Kinerja Bagian Umum Berbasis Motivasi Kerja dan Budaya Organisasi pada Intansi X - Prayoga, Sapta; Rachmat Mulyana, Aam (IPM2KPE, 2024)
This study aims to investigate the relationship and efforts to improve performance based on work motivation and organizational culture. The research method used is quantitative with data collection through library research and field research using interviews, questionnaires, and documentation. The data analysis method involves a descriptive and associative approach, with multiple regression analysis techniques using SPSS software version 25. The results of the study indicate that work motivation and organizational culture have a partial positive effect. Simultaneously affect performance in the general section of agency x. The conclusion is that the respondents' responses to work motivation, organizational culture, and the perception of direct superiors towards employee performance in the general section of agency X are in the sufficient category, with work motivation and organizational culture partially and simultaneously affecting performance, where success and stability are the highest sub-variables, while opportunities for advancement, attention to detail, and punctuality are the lowest sub-variables. Keywords: Organizational Culture, Performance, Work Motivation